2016
DOI: 10.18632/oncotarget.9988
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating lymphocytes in breast cancer predict the response to chemotherapy and survival outcome: A meta-analysis

Abstract: Tumor-infiltrating lymphocytes (TILs) influence tumor prognosis and the chemotherapeutic response. Here, we quantified the clinical relevance of TILs, including the effect of TILs on lymphocyte subpopulations and assessed their consistency in breast cancer. We searched published literature from January 2000 to January 2016. The main parameters analyzed were pathological complete response (pCR) and survival outcome following chemotherapy in patients with breast cancer. Pooled odds ratio (OR) or relative risk (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 33 publications
(15 reference statements)
4
79
0
5
Order By: Relevance
“…In the present study, mRNA expression of CD4, CD8, and FOXP3 was not different according to HER2 status of the TCGA dataset, but there was a significant correlation between T-cell markers. In addition, previous evidence have supported the prognostic and predictive roles of TILs in breast cancers [13142223]. Our study also suggested a possible prognostic role of T-lymphocyte markers measured at mRNA levels in HER2-positive tumors.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, mRNA expression of CD4, CD8, and FOXP3 was not different according to HER2 status of the TCGA dataset, but there was a significant correlation between T-cell markers. In addition, previous evidence have supported the prognostic and predictive roles of TILs in breast cancers [13142223]. Our study also suggested a possible prognostic role of T-lymphocyte markers measured at mRNA levels in HER2-positive tumors.…”
Section: Discussionsupporting
confidence: 85%
“…There is a growing interest in quantifying and reporting total TILs in BC and their different subpopulations in clinical practice, owing to their prognostic and possibly predictive value for immunotherapies. 23,24 In this study, a large cohort with long-term clinical follow-up was used to assess the expression pattern of different immune cell subtypes in BC as well as their association with patient outcome and tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, FOXP3+ cells were associated with a worse prognosis, and have been reported to be correlated with intratumour and tumour‐adjacent stromal compartments . Moreover, the distribution and prognostic significance of TILs is variable among BC molecular classes; they have significant prognostic value in the HER2‐positive and triple‐negative/basal‐like BC class, but not in ER‐positive luminal tumours …”
Section: Bc Intratumour Heterogeneitymentioning
confidence: 99%
“…31 Moreover, the distribution and prognostic significance of TILs is variable among BC molecular classes; they have significant prognostic value in the HER2-positive and triple-negative/basallike BC class, but not in ER-positive luminal tumours. 32,33…”
Section: Bc Intratumour Heterogeneitymentioning
confidence: 99%